Carvão ativado de Capim Annoni (Eragrostis Plana Nees) preparado por pirólise assistida em forno micro-ondas com ativação química e aplicação na remoção de contaminantes orgânicos emergentes de solução aquosa - (:unkn) unknown (Universidade Federal do Pampa, 2019)
The present study describes the preparation, characterization and application of activated carbon from Annoni Grass (Eragrostis plana Nees) via microwave oven pyrolysis and chemical activation for the removal of two emerging organic contaminants Caffeine (CAF) and 2-Nitrophenol (2NF) from aqueous solution. The process of preparation of the activated carbon consisted of the following steps: chemical activation of the precursor material with zinc chloride (ZnCl2), microwave oven pyrolysis using a power of 1300 watts for 5.30 minutes under nitrogen flow and leaching of the inorganic compounds with HCl 6 mol L-1. O activated carbon of Eragrostis plana Nees (CAEPN) was characterized by the following analytical techniques: Vibrational Spectroscopy in the Infrared Region with Fourier Transform (FT-IR), Elementary Analysis (CHNO), Scanning Electron Microscopy (SEM), Isotherms of Nitrogen adsorption/desorption using the BET and BJH mathematical methods, Thermogravimetric Analysis (TGA), Boehm Titration and Zero Load Point (pHPCZ). The CAEPN has a surface area of 1250 m2g-1 with a predominantly mesoporous structure. The adsorption tests were performed by the batch procedure at a temperature of 25 °C. Important parameters that influence the maximum adsorption capacity as amount of adsorbent mass, contact time between adsorbent and adsorbate, solution pH and initial adsorbate concentration were investigated. The maximum adsorption capacity for CAF and 2NF were obtained at pH 7. The equilibrium condition was reached within 30 minutes for both molecules. The amount of adsorbent mass required to obtain the maximum adsorption capacities for CAF and 2NF was 70.0 mg / 20.0 mL. The non-linear equilibrium models Langmuir, Freundlich, Liu were used to describe the mechanism of adsorbent-adsorbate interaction. The Liu model is the one that best fit the experimental data. Based on the Liu model the maximum adsorption capacity (Qmax) was 235.5 mg g-1 for CAF and 255.8 mgg -1 for 2NF. The adsorption kinetics were obtained from the kinetic models of pseudo-first order, pseudo-second order and fractional order of Avrami. The model of fractional order of Avrami was that better describes the kinetics of adsorption for both molecules presenting values closer to the unit R2 and the lowest values for SD. The results obtained show the viability of Annoni Grass application as a precursor material for the production of activated carbon and also show that activated carbon from Annoni Grass (CAEPN) can be used for efficient removal of emerging contaminants such as CAF and 2NF from aqueous solution. Keywords: Activated Carbon; Pyrolysis in a Microwave Oven; Annoni Grass (Eragrostis plana Nees); Removal of Emerging Organic pollutants (Caffeine and 2-Nitrophenol).
Keywords: Engenharia; Carvão Ativado; Capim Annoni (Eragrostis plana Nees); Engineering; Activated Carbon; Annoni Grass (Eragrostis plana Nees); CNPQ::ENGENHARIAS